Pengaruh Temperatur Tuang Terhadap Struktur Mikro Dan Kekerasan Hasil Coran Kuningan Pada Pengecoran Evaporative - Anas, Faris Fauzi; Sugita, I Ketut Gede; Priambadi, I G N (Teknik Desain Mekanika, 2022)
Abstract Brass is a metal alloy that is widely applied to engineering and craft equipment, one of which is decorative bells. The complicated shape of the craft causes frequent defects in castings that are not suitable, the evaporative casting method was chosen because the mold pattern can be formed according to the object with good accuracy. and violence. The brass casting process is carried out with a mold pattern made of expanded polystyrene foam with densities of 0.012, 0.014, 0.016, and 0.018 g/cm3, casting is carried out with variations in casting temperatures of 900, 950 and 1000?. The pouring temperature and the density of expanded polystyrene foam affect the hardness, the highest hardness value is achieved at a density pattern of 0.012 gr/cm3 with a pouring temperature of 900?, hardness of 394.94 HV, while the lowest hardness value is achieved at a pattern density of 0.014 gr/cm3 with a pouring temperature of 1000? hardness 377.57 HV. The results of the observation of the microstructure of brass metal (Cu60% and Zn40%) show that at low casting temperatures, small crystal grains with a and ? ' phases dominate. Keywords: Evaporative Casting, Polystyrene Foam, Hardness, Microstructure